Monitoring, evaluation, and learning tracking report: Site specific fertilizer advisory in the mixed highland farming systems in Ethiopia - Tigabie, Abiro; Desta, Gizaw; Desalegn, Henok; Legesse, Gizachew; Agegnehu, Getachew (International Crops Research Institute for the Semi-Arid Tropics, 2025)
The site-specific fertilizer advisory tool was developed to provide farmers with precise, landscape-driven nutrient management recommendations to produce teff, wheat, sorghum, and maize. Its main objective is to optimize fertilizer use efficiency, enhance crop productivity, and improve economic returns under Ethiopia’s diverse agroecological conditions. Field events and training sessions were organized collaboratively by ICRISAT (36%) and the Ministry of Agriculture through the local extension services (64%). These sessions targeted smallholder farmers and included piloting and scaling of the advisory tool in farmer field conditions. This multi-actor engagement strengthened the quality, reach, and sustainability of the piloting and scaling activities, ensuring that both technical and local perspectives were integrated into the process.